A Curriculum of a Subject of Enneagram for Developing Key Competency of University Students - Jongjin Park (International Journal of Advanced Culture Technology(IJACT), 2022)
This paper is to propose a curriculum of a subject of Enneagram which is to be open to develop key competency of university students. In the modern days of the 4th industrial revolution universities are being called for key competency-based education and innovation in education. Universities suggested various key competencies according to the university's founding philosophies. And they have been reorganizing the liberal arts curriculum in a way that it can reinforce key competencies of the students in the aspect of liberal arts education. In this paper, an example of C university which has 3 key competencies such as, citizenship, character, and creative intelligence was presented. Enneagram is a good candidate for developing self-development which is sub-competency of character.